Implementation of Culture-based Character Education Management through the Application of Blended Learning as a Source of Social Sciences Learning (IPS) - Iskandar,; Misnah,; Andi Baso Malla, Hamlan; Bauratu,; Herlina, (International Journal of Psychosocial Rehabilitation, 2020)
This research is motivated by environmental damage, the phenomenon of derailment of moral values and ethics, and the strengthening of violence caused by humans. In this context, efforts are needed to cultivate the local ecological wisdom values of local culture as an effort to inherit culture towards students. The focus of this research is to promote the management of education based on the local culture of the Kaili ethnic community as a source of learning. Blended learning technology is present as a medium that can be used to help convey information in the form of text, sound, images, or a combination of all these media. This study aims to (1) describe the steps to implement the management of culture-based character education at Sigi 1 Middle School; (2) identify dominant character values in blended learning; and (3) describe local cultural values that are relevant to the management of character education. This study uses a one-shot case study pre-experimental design (non-design) method with the basis of thinking that this study is intended to describe the implementation procedures for culture-based character education management with the application of blended learning. Data collection is done through observation and interviews; data analysis uses descriptive statistical themes (Sugiyono, 2015). The results of the study show that (1) the steps for implementing the management of culture-based character education in SMP 1 Sigi consist of planning, organization, implementation, and supervision; 2) the dominant character values in blended learning are responsibility, independence, honesty, environmental care, social care, and hard work; 3) Kaili ethnic local culture that is relevant to the management of character education is an ombo, which is the local wisdom of environmental conservation.